The Effect of Social Influence and Brand Image on Brand Awareness and Purchase Intention Study Case - Joshua, Leonard (LPPM of NAROTAMA UNIVERSITY, 2025)
This study examines the relationships between social influence, brand image, brand awareness, and purchase intention in consumer behavior. The primary goal is to analyze how social influence and brand image contribute to brand awareness and purchase intention. By exploring these dynamics, the research offers insights into consumer decision-making processes. Using empirical analysis and statistical techniques, the study provides actionable implications for marketers aiming to enhance brand awareness and drive purchase intention in today's competitive market. The findings reveal that brand image has the strongest correlation with purchase intention (H4) with a t-statistic of 6.013. Significant relationships are also found between social influence and brand awareness (H1) with a t-statistic of 5.050, brand awareness and purchase intention (H5) with a t-statistic of 3.536, and brand image and brand awareness (H2) with a t-statistic of 3.297. Conversely, the relationship between social influence and purchase intention (H3) is not significant, indicated by a t-statistic of 0.503. Thus, hypotheses for H1, H2, H4, and H5 are accepted, while H3 is rejected. This study enriches existing knowledge by clarifying the relationships between social influence, brand image, brand awareness, and purchase intention. These insights are crucial for marketers who aim to leverage social influence and brand image to boost brand awareness and drive purchase intention. The findings highlight the pivotal role of brand image in influencing purchase decisions and the importance of social influence in building brand awareness, offering a strategic framework for effective marketing strategies.